Cover Feature: Cooperativity‐Driven Reactivity of a Dinuclear Copper Dimethylglyoxime Complex (Chem. Eur. J. 22/2023). Issue 22 (23rd March 2023) - Petrikat, Raphael I.; Steiger, Sophie T.; Barani, Elham; Boden, Pit J.; Huber, Maximilian E.; Ringenberg, Mark R.; Niedner‐Schatteburg, Gereon; Fink, Karin; Becker, Sabine
Abstract : Cooperativity at the crossroad : The two copper centers in the dinuclear copper(II) dimethylglyoxime complex work in concert to facilitate ligand hydrolysis that yields butane‐2, 3‐dione monoxime and NH2 OH. The fate of NH2 OH depends on the solvent used, in CH3 CN, for example, NH2 OH is oxidized to N2 O yielding [Cu(CH3 CN)4 ] + as reduced species. In ethanol, however, NH2 OH is reduced to NH4 +, which in turn yields acetaldehyde as oxidized species. More information can be found in the Research Article by S. Becker and co‐workers (DOI: 10.1002/chem.202203438 ).